Landscape archaeology, sustainability and the necessity of change. Issue 4 (7th August 2020) - Turner, Sam; Kinnaird, Tim; Koparal, Elif; Lekakis, Stelios; Sevara, Christopher
ABSTRACT: For future landscapes to be sustainable, significant changes in land-use and management practices will be needed. This article argues that landscape archaeology can make distinctive contributions to sustainability in two ways: firstly, by researching what were and were not sustainable ways of life in the past, and secondly by using this knowledge to explain how landscapes of the past differed to those in the present, and in doing so to disrupt the invented connections between past societies, tradition, heritage and conservation. The article draws on three case-studies in China, the Mediterranean and the UK to suggest that archaeological knowledge could be used to help stakeholders imagine future landscapes which are better and more sustainable than those of today. To succeed archaeologists will need to make deeper commitments to transdisciplinary work.